2023
DOI: 10.1186/s40779-022-00437-5
|View full text |Cite
|
Sign up to set email alerts
|

Adipose tissue macrophages: implications for obesity-associated cancer

Abstract: Obesity is one of the most serious global health problems, with an incidence that increases yearly and coincides with the development of cancer. Adipose tissue macrophages (ATMs) are particularly important in this context and contribute to linking obesity-related inflammation and tumor progression. However, the functions of ATMs on the progression of obesity-associated cancer remain unclear. In this review, we describe the origins, phenotypes, and functions of ATMs. Subsequently, we summarize the potential mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 178 publications
1
11
0
Order By: Relevance
“…The observed focal changes at both sampling points in sea water (day 369 and 537) aligned with the histological descriptions of RFC and MFC provided by Bjørgen et al, 2019 andBjørgen et al, 2020. RFC were present in all experimental groups and exhibited simi- tissue of obese humans due to elevated levels of pro-inflammatory mediators (Li et al, 2023;Page et al, 2011). Inflammation of adipose tissue can potentially be induced by hypoxia resulting from adipocytes hypertrophy (Trayhurn et al, 2008).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The observed focal changes at both sampling points in sea water (day 369 and 537) aligned with the histological descriptions of RFC and MFC provided by Bjørgen et al, 2019 andBjørgen et al, 2020. RFC were present in all experimental groups and exhibited simi- tissue of obese humans due to elevated levels of pro-inflammatory mediators (Li et al, 2023;Page et al, 2011). Inflammation of adipose tissue can potentially be induced by hypoxia resulting from adipocytes hypertrophy (Trayhurn et al, 2008).…”
Section: Discussionsupporting
confidence: 77%
“…Additionally, an inflammatory state within the adipose tissue induced by adipocytes themselves could lead to recruitment of inflammatory cells. Reports have indicated an increase in recruited macrophages within adipose tissue of obese humans due to elevated levels of pro‐inflammatory mediators (Li et al, 2023; Page et al, 2011). Inflammation of adipose tissue can potentially be induced by hypoxia resulting from adipocytes hypertrophy (Trayhurn et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The authors utilized a human co-culture system to study the paracrine interactions and demonstrated that pro-inflammatory macrophage-conditioned media intensified the crosstalk between breast cancer cells and adipocytes, causing the breast cancer cells to become more aggressive (Vallega et al 2022). The exact molecular mechanisms underlying this interaction are still unclear but are likely multifactorial and related to the exchange of dysfunctional metabolites, disproportionate cytokine and growth factor production, and transfer of extracellular vesicle cargo (Vallega et al 2022, Li et al 2023. A better understanding of the properties and functions of dysregulated ATMs in obesity-diabetes is required before specific enzymes and/or pathways can be targeted for therapeutic intervention.…”
Section: Monocytes/macrophagesmentioning
confidence: 99%
“…1 and 2). This low-grade chronic metabolic inflammation should not be neglected as it is significantly associated with all-cause mortality in the general population (Fest et al 2019), negatively impacts insulin sensitivity (Blaszczak et al 2020), and increases the risk for cancer development (Li et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Like all complex organs, there are intracellular communications between the cells in both normal tissues and in the cancers that derive from these organs. For example, adipose tissue macrophages may be influenced by the abnormal microenvironment in obesity and contribute to aggressive behavior of tumors, metastasis, and an im- [30]. Similarly, cross talk from the adipocytes in obesity also seems to promote fibrosis, aggressiveness and metastasis in breast cancer and other obesity-associated cancers [31].…”
Section: Correlation Between Obesity and Breast Cancermentioning
confidence: 99%